Electric power system applications of optimization - Momoh, James A. 1950- (CRC Press, 2009)
Providing a broad treatment of both theoretical and application aspects of power systems operation and planning, this edition presents new functions involving market programs, pricing, reliability, and advances in intelligent systems with implemented algorithms and illustrative examples.